The Federalist - Hamilton, Alexander, 1757-1804.; Madison, James, 1751-1836.; Jay, John, 1745-1829.; Ball, Terence (Cambridge, U.K. ; New York : Cambridge University Press, 2003)
"The Federalist represents one side of one of the most momentous political debates ever conducted: whether to ratify, or to reject, the newly drafted American constitution. To understand the debate properly requires attention to opposing Antifederalist arguments against the newly drafted constitution, and this new and authoritative student-friendly edition presents in full all eighty-five Federalist papers written by the pseudonymous "Publius" (Hamilton, Madison, and Jay), along with the sixteen letters of "Brutus," the prominent but still unknown New York Antifederalist who was Publius's most formidable foe
Presents all eighty-five Federalist papers written by the pseudonymous Publius, along with the sixteen letters of Brutus, the still unknown New York Antifederalist.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (Cambridge, viewed on March 20, 2025).
English.
eBooks on EBSCOhost
Keywords: Federalist; Federalist; Constitutional history -- United States; United States -- Politics and government -- 1783-1789.; Histoire constitutionnelle -- États-Unis.; États-Unis -- Politique et gouvernement -- 1783-1789.; LAW -- Constitutional; LAW -- Public; Constitutional history; Politics and government; United States; 1783-1789; Jura -- Jura